Design and development of e-learning environment for deaf students in learning nuclear energy - Mohd. Hashim, Mohd. Hisyamuddin (2016)
This research aims to develop an e-learning environment for deaf students in learning Nuclear Energy. The performance level of deaf students, as well as learning patterns that have emerged from their activities within the developed e-learning environment were examined. This research utilizes a quantitative research design by using questionnaires and performance tests, as well as additional qualitative data from interviews. Data was attained from two different sets of questionnaires, the log data files from the e-learning, performance tests, and the interview sessions. Questionnaires were initially distributed to 52 deaf students from a school in Johor Bahru to examine their e-learning readiness. Next, an e-learning environment for the deaf students was developed with the implementation of sign language videos as the main feature. The same 52 deaf students were given another questionnaire to examine the usability and motivation to learn using the developed e-learning environment. After that, 20 Form four deaf students were involved in using the developed e-learning environment in order to examine their performance and learning patterns that emerged from their activities within the e-learning environment. Data were analyzed through descriptive analysis (mean and standard deviation), inferential analysis (paired-samples t-test, effect size, and power analysis) and data mining (decision tree). Data mining analysis using the decision tree technique was used to examine the learning patterns by the deaf students when using the developed e-learning environment based on their performance level. The results from descriptive analysis show that the deaf students have a moderate level of elearning readiness, as well as the usability and motivation to learn using the developed e-learning environment. The results from the paired-samples t-test show that there is a statistically significant difference between the pre-test and the post-test scores (p<0.05). The meta-analysis of the t-test shows that the treatment has a large effect size on the deaf students’ performance, while the results from the power analysis show that if this treatment is repeated, similar results will be acquired. Eleven learning patterns were emerged based on three increment categories of the deaf students’ performance. This research found that the learning patterns of deaf students who achieved the best increment category of performance accessed the sign language videos more frequently compared to other deaf students.